MEWUJUDKAN MASYARAKAT MORAL BERDAYA SAING TINGGI - Sayuti Hasibuan (Muhammadiyah University Press, 2005)
The development experience since Indonesian independence generally shows that welfare is still out of reach. It shows that there is a need to replace the basic ideology of development operational from material to human beings. The operational vision need to be changed from creating a welfare nation to creating a morally nation that has high competency since the latter measurement comprise more, materially or non-materially.In this writing, writer stated that the absolute requirement for the development success of developing countries, including Indonesia, is strategy orientation changes from outward looking to inward looking; from basic operational ideology of material to human and humanity ideology.